An Error Analysis Of Using Conditional Sentences: A Case Study Of SMK Negeri 1 Aceh Barat Daya - Silfa Rahimi; Nuzulul Isna (Journal Informatic, Education and Management (JIEM), 2025)
The purpose of this study is to identify the types of errors and the most frequent errors made by students in using conditional sentences. This research employs a qualitative approach, focusing on error analysis. The subjects of the study are 32 students from SMK Negeri 1 Aceh Barat Daya. Data were collected using a test consisting of 20 questions. The analysis revealed that the highest number of errors occurred in Type 3 conditional sentences, with 72 instances (34%), followed by Type 1 with 61 errors (29%), Type 2 with 41 errors (20%), and Type 0 with 35 errors (17%). In terms of error categories, misordering was the most dominant, with 73 errors (35%), followed by misformation with 53 errors (25%), omission with 51 errors (24%), and addition with 32 errors (15%). In conclusion, the findings indicate that Type 3 conditional sentences and misordering are the most significant challenges faced by students in mastering conditional sentence structures.